Chinese Black Truffle (Tuber indicum) Alters the Ectomycorrhizosphere and Endoectomycosphere Microbiome and Metabolic Profiles of the Host Tree Quercus aliena - Li, Qiang; Yan, Lijuan; Ye, Lei; Zhou, Jie; Zhang, Bo; Peng, Weihong; Zhang, Xiaoping; Li, Xiaolin (Frontiers in Microbiology, 2018)
Truffles are one group of the most famous ectomycorrhizal fungi in the world. There is little information on the ecological mechanisms of truffle ectomycorrhizal synthesis in vitro. In this study, we investigated the ecological effects of Tuber indicum – Quercus aliena ectomycorrhizal synthesis on microbial communities in the host plant roots and the surrounding soil using high-throughput sequencing and on the metabolic profiles of host plant roots using metabolomics approaches. We observed an increase in the diversity and richness of prokaryotic communities and a decrease in richness of fungal communities in the presence of T. indicum. The microbial community structures in the host roots and the surrounding soil were altered by ectomycorrhizal synthesis in the greenhouse. Bacterial genera Pedomicrobium, Variibacter, and Woodsholea and fungal genera Aspergillus, Phaeoacremonium, and Pochonia were significantly more abundant in ectomycorhizae and the ectomycorrhizosphere soil compared with the corresponding T. indicum-free controls (P < 0.05). Truffle-colonization reduced the abundance of some fungal genera surrounding the host tree, such as Acremonium, Aspergillus, and Penicillium. Putative prokaryotic metabolic functions and fungal functional groups (guilds) were also differentiated by ectomycorrhizal synthesis. The ectomycorrhizal synthesis had great impact on the measured soil physicochemical properties. Metabolic profiling analysis uncovered 55 named differentially abundant metabolites between the ectomycorhizae and the control roots, including 44 upregulated and 11 downregulated metabolites. Organic acids and carbohydrates were two major upregulated metabolites in ectomycorhizae, which were found formed dense interactions with other metabolites, suggesting their crucial roles in sustaining the metabolic functions in the truffle ectomycorrhization system. This study revealed the effects of truffle-colonization on the metabolites of ectomycorrhiza and illustrates an interactive network between truffles, the host plant, soil and associated microbial communities, shedding light on understanding the ecological effects of truffles.